El imaginario femenino emeritense y el advenimiento del movimiento sufragista en Venezuela (1936-1947) [Debates] - Samudio A., Edda O. (2020)
The article explores the participation of women in Venezuela’s political organizations in the period following the death of strongman President Juan Vicente Gómez between the mid-thirties and forties, a historical period during which the modern nation-state was established. In this context, women’s participation in suffrage is examined, on the basis of which a critique is developed of the hero/patriarchal male, rooted in Venezuela’s historiographical perspective. It reveals the minds and imagination of women and provides evidence of the legacy left by women in the Andean area and their contributions to the region’s sociopolitical transformation, challenging conventional historical narratives.